Inhibitory Receptor Expression on T Cells as a Marker of Disease Activity and Target to Regulate Effector Cellular Responses in Rheumatoid Arthritis - Onofrio, Luisina Inés (2018)
Objective: Inhibitory receptors are essential for the regulation of effector immune responses and may play critical roles in autoimmune diseases. We evaluated whether inhibitory receptor expression on T cells from patients with rheumatoid arthritis (RA) were correlated with immune activation, disease activity, and response to treatment, as well as whether inhibitory receptor–mediated pathways were functional. Methods: Using flow cytometry, we performed extensive phenotypic and functional evaluation of CD4+ and CD8+ T cells from the blood and synovial fluid (SF) of RA patients ex vivo and after culture. The relationship of each parameter with the Disease Activity Score in 28 joints using the erythrocyte sedimentation rate (DAS28-ESR) and response to treatment was examined. Results: In RA patients with low levels of T cell activation, inhibitory receptor expression showed an inverse relationship with the DAS28-ESR. The frequency of T cells expressing multiple inhibitory receptors was reduced in untreated RA patients but returned to normal levels in treated patients. RA patients who responded to treatment showed an augmented frequency of inhibitory receptor–expressing T cells that correlated with reduced inflammatory cytokine production in comparison to nonresponders. Higher frequencies of effector and memory T cells that expressed multiple inhibitory receptors were seen in SF than in peripheral blood. Notably, inhibitory pathways were operative in blood and synovial T cells from all RA patients, although cells from nonresponder patients were less sensitive to inhibition. Conclusion: Inhibitory receptor expression on T cells from RA patients is inversely correlated with effector T cell function and disease activity and may predict response to treatment. Furthermore, different inhibitory pathways are functional and cooperatively suppress synovial T cells, providing a rationale for new treatment strategies to regulate acute local inflammation.